The changes of cardiac energy metabolism with sodium-glucose transporter 2 inhibitor therapy - Su, Sha; Ji, Xiang; Li, Tong; Teng, Yu; Wang, Baofu; Han, Xiaowan; Zhao, Mingjing (Frontiers in Cardiovascular Medicine, 2023)
Background/aims To investigate the specific effects of s odium-glucose transporter 2 inhibitor (SGLT2i) on cardiac energy metabolism. Methods A systematic literature search was conducted in eight databases. The retrieved studies were screened according to the inclusion and exclusion criteria, and relevant information was extracted according to the purpose of the study. Two researchers independently screened the studies, extracted information, and assessed article quality. Results The results of the 34 included studies (including 10 clinical and 24 animal studies) showed that SGLT2i inhibited cardiac glucose uptake and glycolysis, but promoted fatty acid (FA) metabolism in most disease states. SGLT2i upregulated ketone metabolism, improved the structure and functions of myocardial mitochondria, alleviated oxidative stress of cardiomyocytes in all literatures. SGLT2i increased cardiac glucose oxidation in diabetes mellitus (DM) and cardiac FA metabolism in heart failure (HF). However, the regulatory effects of SGLT2i on cardiac FA metabolism in DM and cardiac glucose oxidation in HF varied with disease types, stages, and intervention duration of SGLT2i. Conclusion SGLT2i improved the efficiency of cardiac energy production by regulating FA, glucose and ketone metabolism, improving mitochondria structure and functions, and decreasing oxidative stress of cardiomyocytes under pathological conditions. Thus, SGLT2i is deemed to exert a benign regulatory effect on cardiac metabolic disorders in various diseases. Systematic review registration https://www.crd.york.ac.uk/, PROSPERO (CRD42023484295).